Implementation of Google Forms and Spreadsheet Processing on Mid-Semester Exam Digitization to Support a Paperless Campus - Syafran Nurrahman; Lena Farsiah; Mohammad Ruvi; Hayati Fina Setiani; Iskandar Iskandar (Journal Of Applied Multidisiplinary Studies, 2026)
Digital transformation in higher education has accelerated the adoption of digital learning assessment systems that are more efficient and environmentally sustainable. However, mid-semester examinations (UTS) in many universities continue to rely on paper-based methods, resulting in time-consuming assessment processes and excessive paper consumption. This study evaluates the implementation of a digital examination system based on Google Forms integrated with Google Sheets and Microsoft Excel to improve assessment efficiency while supporting paperless campus initiatives. A descriptive quantitative approach was employed involving 45 undergraduate students. Data were collected through observations, interviews, documentation, and questionnaires, and analyzed using descriptive statistics with instrument validity and reliability testing. The findings indicate that the Google Forms-based examination system reduced grading time for multiple-choice tests from approximately 2–3 hours to less than one minute through automated scoring. Furthermore, integration with Google Sheets and Microsoft Excel streamlined grade recapitulation, minimized human error, and eliminated the need for printed examination materials. Students also reported positive perceptions regarding system usability, accessibility, efficiency, and its contribution to paperless learning practices. These findings suggest that Google Forms provides a practical, cost-effective, and easily implementable digital examination solution for higher education institutions, particularly those with limited technological resources.